2022
DOI: 10.2147/nss.s342922
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine Intake on Cognitive Performance Related to Total Sleep Deprivation and Time on Task: A Randomized Cross-Over Double-Blind Study

Abstract: Introduction It is widely admitted that both total sleep deprivation (TSD) and extended task engagement (Time-On-Task, TOT) induce a cognitive fatigue state in healthy subjects. Even if EEG theta activity and adenosine both increase with cognitive fatigue, it remains unclear if these modifications are common mechanisms for both sustained attention and executive processes. Methods We performed a double-blind counter-balanced (placebo (PCBO) and caffeine (CAF) - 2×2.5 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The electrophysiological correlates of acute caffeine intake have also been widely described with a consensus on its global decreasing effects on EEG powers during cognitive tasks in sleep-deprived and non-sleep-deprived subjects [ 6 , 7 , 8 ] or in resting states with the eyes closed [ 16 ]. In agreement with the literature, we found significant main treatment (caffeine/placebo) effects on theta, alpha, and beta power bands which were reflected by decreasing powers with acute caffeine intake.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The electrophysiological correlates of acute caffeine intake have also been widely described with a consensus on its global decreasing effects on EEG powers during cognitive tasks in sleep-deprived and non-sleep-deprived subjects [ 6 , 7 , 8 ] or in resting states with the eyes closed [ 16 ]. In agreement with the literature, we found significant main treatment (caffeine/placebo) effects on theta, alpha, and beta power bands which were reflected by decreasing powers with acute caffeine intake.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental protocols on total sleep deprivation, vigilant attention, assessed by the psychomotor vigilance task (PVT), is the most affected cognitive capability [ 4 , 5 ]. Changes in the individual EEG alpha and theta power after prolonged wakefulness were also found to be related to subjective sleepiness and PVT performance [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, consumption of caffeine can lead to improved wakefulness and decreased fatigue [ 8 ]. Various studies related to the arousal effects of caffeine in humans and animals have reported prolonged sleep latency and a state of wakefulness [ 9 , 10 , 11 , 12 ]. A recent study reported that coffee is the main source of caffeine, accounting for approximately 80% of total intake of caffeine in adults [ 13 ].…”
Section: Introductionmentioning
confidence: 99%